SOME PROBLEMS OF RUSSIAN LANGUAGE TEACHING IN HIGHER EDUCATION INSTITUTIONS - Мирзалиева Дилдора Бакировна (Western European Studies, 2024)
To solve these problems, teachers are recommended to use textbooks, information and programs created in the study and teaching of the Russian language
Keywords: Teachers; Russian; recommended; information